Frontispiece: "Dial‐In" Emission from a Unique Flexible Material with Polarization Tuneable Spectral Intensity. Issue 59 (22nd October 2019) - Kumar, Rajan; Ray, Subir Kumar; Mukherjee, Saikat; Saha, Sudipta; Bag, Arijit; Ghorai, Pradip Kr.; Ghosh, Nirmalya; Shunmugam, Raja
Abstract : In their Full Paper on page 13514 ff., R. Shunmugam et al. report on the growth of 3D flexible organic film by photon click thiolation. The film showed energy emission tunability, which was further analysed using full polarization Mueller matrix approach. Fluorescence diattenuation and fluorescence polarizing are the two parameters introduced to study the orientational order within the film.